Invisible Violence against Women and Girls with Disabilities: Factors Favoring the Continuation of Forced Sterilization in Chile - Yupanqui Concha, Andrea; Aranda Farias, Cristian Alejandro; Ferrer-Perez, Victoria A. (My University, 2021)
In 2017, Chile was denounced by the United Nations, along with 37 other countries, for the practice of forced sterilizations on women and girls with disabilities. This research explores the views of Chilean activists, professionals, and researchers on the factors that favor the continuation of this practice in the country. Twenty-one informants were interviewed using a qualitative approach based on constructivist grounded theory. The main factors that lead to this type of sterilization were the acceptance of sexual violence and the non-recognition of the violence perpetrated, the absence of a protective state, and the dynamics of abuse of power over women and girls with disabilities. It is concluded that forced sterilization is part of a vast repertoire of violence against women and girls with disabilities, which deepens and perpetuates dynamics of oppression, injustice, and social inequality.
Keywords: chile; disability; forced sterilization; social inequality; violence against women